2011
DOI: 10.1007/s00167-011-1754-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tranexamic acid on blood loss and use of blood products in total knee arthroplasty: a meta-analysis

Abstract: Therapeutic study (Systematic review of Level I studies with inconsistent results), Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
121
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(139 citation statements)
references
References 43 publications
12
121
0
6
Order By: Relevance
“…In THA and TKA, the most notable complication reported in the literature is venous thromboembolism. The vast majority of orthopaedic TXA studies show no increase in the rate of venous thromboembolism events [29][30][31]43,44]. Nishihara, et al is the only study in the recently published literature known to the authors that demonstrated a significant increase in venous thromboembolic events after TXA administration in total joint arthroplasty [18].…”
Section: Oral Usementioning
confidence: 99%
“…In THA and TKA, the most notable complication reported in the literature is venous thromboembolism. The vast majority of orthopaedic TXA studies show no increase in the rate of venous thromboembolism events [29][30][31]43,44]. Nishihara, et al is the only study in the recently published literature known to the authors that demonstrated a significant increase in venous thromboembolic events after TXA administration in total joint arthroplasty [18].…”
Section: Oral Usementioning
confidence: 99%
“…Studies carried out with TXA have reported no increase in the number of complications such as DVT or Pulmonary emboli after TKR surgery. 40,21,22 In the meta-analysis they reviewed 19 clinical studies, Alshryda et al found significant decrease in blood transfusion need with TXA application and stated that there was no increase in the risk of DVT and Pulmonary emboli. 40 Another metaanalysis which assessed the efficiency and reliability of TXA showed decreases in the amounts of blood loss without any increase in thrombo emboli rates.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Especially in recent years, many studies have suggested that the antifibrinolytic agent, Tranexamic Acid (TXA) can considerably reduce blood loss and the need for blood transfusion after TKR surgeries. 21,22 TXA has been applied locally or systemically. [23][24][25] This study was aimed to ascertain the effectiveness of tranexamic acid in minimizing the intra operative and postoperative blood loss in total knee arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…TXA led to a significant reduction in the proportion of patients requiring blood transfusion. 5 Wind TC et all in their study found that there were no transfusions with topical TXA. 6 Sa-ngasoongsong P et all found that the clamping of drain along with tranexamic acid reduce the post-operative blood loss more than 2 the clamping of drain and tranexamic acid alone 7 Soni A et all found that intra-articular tranexamic acid is equally effective as three dose intravenous regimen in reducing blood loss during total knee arthroplasty surgery.…”
Section: Introductionmentioning
confidence: 90%